HUBUNGAN ANTARA PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB DI MTS AL-MA’ARI 03 SINGOSARI KABUPATEN MALANG - Khofidhotur Rofi’; Anwar Sa’dullah; Muhammad Fahmi Hidayatullah (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This study aims to analyze and describe the relationship between online learning and student learning outcomes in Arabic subjects at MTs Al-Ma'arif 03 Singosari Malang Regency. During the covid-19 pandemic, which used to be between teachers and students in one room, face to face in the process of implementing learning and learning, but in this pandemic situation, it was replaced with online learning. Changes in learning methods can also have an impact on learning outcomes, which will be proven through the research methods used by researchers. In this study, researchers used quantitative research using Pearson's product moment correlation technique to determine whether or not there was a relationship between the two variables, assisted by the SPSS application. The main results in this study there is no relationship between the two variables, namely online learning on student learning outcomes.